2016
DOI: 10.12816/0033763
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Insulin Resistance in Rats Treated with Rice Bran Oil

Abstract: Background: insulin resistance (IR) is a pathological condition characterized by inadequate peripheral tissue metabolic response to circulating insulin. It plays pathophysiological role in type 2 diabetes mellitus (T2DM). High dosage of fructose in the diet (60 g/100 g diet) may induce insulin resistance accompanied by deleterious metabolic consequences including hyperglycemia and hyperinsulinemia. Rice bran oil (RBO), is a rich source of antioxidants especially γ-oryzanol, αtocopherols and tocotrienols which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Diminishes in insulin level along with the reduction in glucose and HOMA-IR suggest that RBO acts as a hypoglycemic agent through improving insulin action rather than insulin secretion. These results agree with those of Abd elbast et al [11] and Abd El-Wahab et al [5], who recorded that addition of RBO to high fructose diet-fed rats, improves insulin resistance. The appreciable amount of oleic acid and tocotrienols in RBO may be the causes of glucose reduction and insulin sensitivity in rats fed HFD containing RBO [30,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Diminishes in insulin level along with the reduction in glucose and HOMA-IR suggest that RBO acts as a hypoglycemic agent through improving insulin action rather than insulin secretion. These results agree with those of Abd elbast et al [11] and Abd El-Wahab et al [5], who recorded that addition of RBO to high fructose diet-fed rats, improves insulin resistance. The appreciable amount of oleic acid and tocotrienols in RBO may be the causes of glucose reduction and insulin sensitivity in rats fed HFD containing RBO [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…These bioactive compounds reduce oxidative stress which causes many diseases such as diabetes, cancers, and neurodegenerative diseases [10]. Several studies have demonstrated that RBO possesses hypoglycemic activity [5,11] since chronic exposure to hyperglycemia may induce dysregulation of gene expression that converges on impaired insulin secretion and increased apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rice bran oil (RBO) is characterized by its mild flavor, high smoke point, and long shelf stability, in addition to its high content of linoleic and oleic fatty acids and natural antioxidants such as γ-oryzanol, phytosterols, tocopherols, and tocotrienols (Friedman, 2013;Liang et al, 2014). RBO was reported as a lipid-lowering agent (Abd Elbast, Rashed, Mohamed, Ahmed, & Ahmed, 2016;Berger et al, 2005), which protects against diabetes mellitus (Posuwan et al, 2013), cancers (Shih et al, 2011), brain aging, and neurodegenerative diseases (Stephanie et al, 2013) due to its antioxidant content.…”
Section: Introductionmentioning
confidence: 99%